Levantamento dos solos da sede do Núcleo Pioneiro de Humboldt, Município de Aripuanã, MT - Aloisi, R. R. [UNESP]; Boni, N. R. [UNESP]; Ferreira, M. E. [UNESP] (Instituto Nacional de Pesquisas da Amazônia, 1978)
This work presents a semi-detailed soil survey and results from preliminary data of soils occuring in disforested area near the buildings of the Humboldt Center of Aripuanã County (MT). After preliminary reconnaissance, 3 soil profiles were described and 72 samples were taken an their analysis led to the following classification: Red-Yellow Latosol Dystrophic Weak A medial texture, and Red. Yellow Latosol Dystrophic Weak A clay texture. A simple analysis of that data indicates the use of conservationist proceedures.